MULTIPLE ECONOMETRIC FORECAST OF THE DEVELOPMENT OF SMALL BUSINESS ACTIVITY IN NAVOI REGION - Baqoev Husan Nuriddinovich (Research Parks Publishers, 2020)
This article makes analyses of the multiple econometric forecasts of the development of small business activity in the Navoi region. In this case, both theatrical and analytical analyses were conducted in order to make better analyses of the research as a whole. In conclusion, outcomes and shortcomings were stated to get more detailed information and recommendations as the whole